Solve the equation and check your answer 2.4(3-x)-0.6(2x-3)=0
Answers
Answered by
1
Answer:
Answer :- x=2.5
Step-by-step explanation:
The given equation is
2.4(3-x)-0.6(2x-3)=02.4(3−x)−0.6(2x−3)=0
Using distribution property, we get
7.2-2.4x-1.2x+1.8=07.2−2.4x−1.2x+1.8=0
Now, combine like terms.
9.0-3.6x=09.0−3.6x=0
Add 3.6 on both the sides.
9.0=3.6x9.0=3.6x
Divide both sides by 3.6.
\frac{9.0}{3.6}=x
3.6
9.0
=x
2.5=x2.5=x
Answered by
1
Answer:
wdfs
Step-by-step explanation:
iyo
Similar questions